2019
DOI: 10.1186/s12883-019-1477-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolated hypoglossal nerve palsy from internal carotid artery dissection related to PKD-1 gene mutation

Abstract: BackgroundInternal carotid artery dissection has been well recognized as a major cause of ischaemic stroke in young and middle-aged adults. However, internal carotid artery dissection induced hypoglossal nerve palsy has been seldom reported and may be difficult to diagnose in time for treatment; even angiography sometimes misses potential dissection, especially when obvious lumen geometry changing is absent.Case presentationWe report a 42-year-old man who presented with isolated hypoglossal nerve palsy. High-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The main mechanism involves the formation of dissecting aneurysm that compresses the posterior cranial nerve, resulting in nerve paralysis. 6 , 18 , 19 , 20 , 21 , 22 In this case, the anatomy of the internal carotid artery resulted in an intermural hematoma, which caused stenosis of the vascular lumen and the shedding of the thrombi, which led to symptoms of ischemic stroke. The patient showed symptoms of posterior cranial nerve injury without the occurrence of aneurysm.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The main mechanism involves the formation of dissecting aneurysm that compresses the posterior cranial nerve, resulting in nerve paralysis. 6 , 18 , 19 , 20 , 21 , 22 In this case, the anatomy of the internal carotid artery resulted in an intermural hematoma, which caused stenosis of the vascular lumen and the shedding of the thrombi, which led to symptoms of ischemic stroke. The patient showed symptoms of posterior cranial nerve injury without the occurrence of aneurysm.…”
Section: Discussionmentioning
confidence: 91%
“…Among them, the XII injury of the cranial nerve is the most common, followed by IX, X, and XI. The main mechanism involves the formation of dissecting aneurysm that compresses the posterior cranial nerve, resulting in nerve paralysis 6,18‐22 . In this case, the anatomy of the internal carotid artery resulted in an intermural hematoma, which caused stenosis of the vascular lumen and the shedding of the thrombi, which led to symptoms of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…19 At present, most of the literature of PC1 focuses on the pathogenesis of ADPKD, 20,21 but there are still a few studies on AD. 22 In PKD1 knockout mice, PKD1 downregulation resulted in a series of pathologic alterations in aortic walls of those mice such as latent laeouna and intramural hematoma, which are similar to human AD. 23 It was known that sustained reduction of intracellular Ca(2+) promoted the proliferation and apoptosis of VSMCs.…”
Section: Discussionmentioning
confidence: 97%
“…Spontaneous extracranial ICA dissection associated with ADPKD is extremely rare, with only nine cases reported in the English literature to date, including our patient ( Table 1 ) [ 5 , 6 , 7 , 8 , 9 ]. We analyzed these cases, which included four women and five men with a mean age of 41.1 years.…”
Section: Discussionmentioning
confidence: 99%
“…The reviewed cases and our cases were examined together, demonstrating that the prognosis was favorable in six cases, except for one patient with cerebral infarction, out of the seven total cases in which the prognosis was described ( Table 1 ) [ 22 ]. Strunk et al [ 5 , 6 , 7 , 8 , 9 ] reported that recurrent cervical artery dissection was rare in ordinary spontaneous cervical ICA dissection. On the other hand, as in our case, it is possible to develop arterial dissection at other sites; thus, careful observation of the clinical course is necessary for spontaneous ICA dissection in ADPKD patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%